2021
DOI: 10.7759/cureus.20675
|View full text |Cite
|
Sign up to set email alerts
|

Necrotising Otitis Externa: A Review of Imaging Modalities

Abstract: Necrotising Otitis Externa (NOE) has often posed some challenges in view of diagnosis and management by clinicians. One such challenge is the appropriate and timely use of imaging techniques since its use is critical not only in diagnosis but also in determining the extent and resolution of the disease. Hence, doctors in both primary and secondary health care need to be familiar with presenting symptoms while specialists need to be appraised of advances in imagining techniques in diagnosis and management of NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
5
3
0
1
Order By: Relevance
“…These findings are in accordance with those of Yassin et al [14] in Egypt, Rahman and Nhan et al [17] and Khan A.F.M. et al [15] in Bangladesh, Anwarullah and Jayader et al [18] in Visakhapatnam, India, and then in Myanmar [19]. Hawke et al [20] in Canada, Mungliston et al [21] in London had also shown similar incidence in male and female patients in their studies.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are in accordance with those of Yassin et al [14] in Egypt, Rahman and Nhan et al [17] and Khan A.F.M. et al [15] in Bangladesh, Anwarullah and Jayader et al [18] in Visakhapatnam, India, and then in Myanmar [19]. Hawke et al [20] in Canada, Mungliston et al [21] in London had also shown similar incidence in male and female patients in their studies.…”
Section: Resultssupporting
confidence: 90%
“…In our study population, the maximum number of patients were Labourer constituting 30%, who were engaged to work in hot, humid, and overcrowded places, maintaining very poor personal hygiene. Studies of Yassin et al [14] in Egypt and Khan and Rahman et al [17], and Khan A.F.M et al [15] in Bangladesh also showed Similar results while than of Myanmar had shown higher prevalence among children, school teachers, and office staff [19]. In the present study, educational status showed that only 2.5% were illiterate, and the remaining patients were literate, varying from primary education to master level.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Med MRskanning kan man påvise spredning af infektion til bløddele relateret til temporalbenet, absces, flegmone og sinustrombose. PET/CT kan anvendes til at følge forløbet af sygdommen[19].…”
unclassified